Representation Of Ferdinand De Saussure's Semiotics In The Film Jakarta VS Everybody - Sinaga, Winda Sari (International Journal of Cultural and Social Science, 2023)
The purpose of this research is to find out the semiotic representation of Ferdinand De Saussure in the film Jakarta vs Everybody, to find out the signifier conveyed in the film Jakarta vs Everybody, to find out the signified conveyed in the film Jakarta vs Everybody. This type of research is descriptive qualitative using Ferdinand de Saussure's semiotic analysis method. In his method he develops two systems, namely the signifier, the signified and the meaning contained and conveyed in it. This film tells the story of the life of a young man from Padang, West Sumatra who migrates to the metropolitan city, namely Jakarta to fulfill his dream. But instead of getting a life according to what he wished for, Dom instead gets a rather winding and complicated life. Early in his life in Metropolitan City, Dom met a drug dealer and offered him to become a drug courier. The results of the study draw conclusions regarding the signifier and signified and the meaning of the film, namely this film is more directed towards a moral message, which can be seen from the scenes per episode.